The feasibility, acceptability and sustainability of nurse-led chronic disease management in Australian general practice: The perspectives of key stakeholders - Hegney, Desley; Patterson, E.; Eley, D.; Mahomed, R.; Young, J. (Wiley-Blackwell Publishing Asia, 2013)
This was the first Australian study investigating the acceptability, feasibility and sustainability of a nurse-led model of chronic disease management in general practice. A concurrent mixed-methods design was used within a 12-month intervention of nurse-led care in three general practices. Adult patients with type 2 diabetes, hypertension and/or stable ischaemic heart disease were randomized into nurse-led or standard care. Semi-structured interviews explored perceptions of key stakeholders towards this model including patients in the nurse-led arm, and all practice staff pre- and posttrial. The data were thematically analysed and the emergent themes were: importance of time; collaborative relationships; nurse job satisfaction, confidence and competence; patient self-management and choice. Our findings showed that nurses provided chronic disease management that was acceptable, feasible and sustainable. The collaborative involvement of doctors was intrinsic to patient acceptability of nurse-led care that facilitated job satisfaction, and therefore retention and growth within this nursing speciality.